2021
DOI: 10.1155/2021/5584447
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Degradation of Gasdermin D Protects against Nucleus Pulposus Cell Pyroptosis and Retards Intervertebral Disc Degeneration In Vivo

Abstract: Intervertebral disc degeneration (IDD) is the primary culprit of low back pain and renders heavy social burden worldwide. Pyroptosis is a newly discovered form of programmed cell death, which is also involved in nucleus pulposus (NP) cells during IDD progression. Moderate autophagy activity is critical for NP cell survival, but its relationship with pyroptosis remains unknown. This study is aimed at investigating the relationship between autophagy and pyroptotic cell death. The pyroptosis executor N-terminal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…IDD is a complex process in which resident pyroptosis promotes its development [ 33 , 34 ]. It has been identified that there is a considerable accumulation of inflammatory factors in IDD, leading to the accumulation of NLRP3, caspase-1, GSDMD, and other pyroptosis factors and eventually cell death [ 35 , 36 ]. Further investigation of the role of pyroptosis-related genes in IDD is consequently required.…”
Section: Discussionmentioning
confidence: 99%
“…IDD is a complex process in which resident pyroptosis promotes its development [ 33 , 34 ]. It has been identified that there is a considerable accumulation of inflammatory factors in IDD, leading to the accumulation of NLRP3, caspase-1, GSDMD, and other pyroptosis factors and eventually cell death [ 35 , 36 ]. Further investigation of the role of pyroptosis-related genes in IDD is consequently required.…”
Section: Discussionmentioning
confidence: 99%
“…At present, more and more evidences show that pyrolysis plays an important role in the pathogenesis of degenerative disc disease. Therefore, we explored the effect of PDGF-BB on the pyrolysis of nucleus pulposus cells induced by IL-1β (Bai et al, 2020;Liao et al, 2021;Zhou et al, 2021). We found that PDGF-BB can effectively inhibit the activation of pyroptosis-related signals and the production of pyroptosis products in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the cell membrane is crucial for the release of pro-inflammatory factors, reducing the generation of GSDMD, and increasing its degradation can prevent the pore-forming damage to the cell membrane by GSDMD-N generated by cleavage. Through in vitro experiments, Liao et al [ 129 ] found that in an activated autophagy system, P62/SQSTM1 can selectively degrade GSDMD-N as an autophagy receptor, prevent GSDMD-N from accumulating on the cell membrane, and inhibit the pyroptosis of degenerated human NP cells. This correlates autophagy with pyroptosis and enhances the selective autophagy of pro-pyroptotic proteins.…”
Section: Link Between Caspases and Inflammatory Response In Ivddmentioning
confidence: 99%
“…These two inhibitors have been used in clinical studies in rheumatoid arthritis and OA [ 162 ]. In IVDD, delivery of VX-765 inhibits inflammasome activation and pyroptosis, thereby improving IVDD progression in vivo [ 129 ]. Although VX-765 has a good therapeutic effect on many diseases, it has certain toxic side effects and needs to be further improved for clinical applications.…”
Section: Caspase Inhibitorsmentioning
confidence: 99%